Bound polyphenol extracted from jujube pulp triggers mitochondria-mediated apoptosis and cell cycle arrest of HepG2 cell in vitro and in vivo. (February 2019) - Shan, Shuhua; Xie, Yue; Zhao, Huiling; Niu, Jinping; Zhang, Sheng; Zhang, Xiaoli; Li, Zhuoyu
Graphical abstract: Highlights: JPBP exhibits prominent anti-hepatoma activity in vitro and in vivo. JPBP decreases the level of MMP via blocking AKT/NF-κB/Bcl-2 signal axis. JPBP initiates mitochondria-mediated intrinsic apoptotic pathway in HepG2 cells. JPBP suppresses cell proliferation by promoting HepG2 cell cycle arrest in S phase. JPBP has potential as an effective and non-toxic agent against liver cancer. Abstract: Chinese jujube which contains many nutrients, contributes to a healthy diet. Jujube pulp extracts are rich in polyphenol compounds exhibiting admirable pharmacological activities. In present, free and bound polyphenols extracted from jujube pulp were named JPFP and JPBP, respectively. Interesting, we found only JPBP exhibited prominent anti-tumor activity in HepG2 cells, and especially, it also had the same effect in nude mice tumor model. Further, the study showed that p-Coumaric acid and ferulic acid might be main active components in JPBP. Mechanically, JPBP decreased mitochondrial membrane potential (MMP) via blocking AKT/NF-κB/Bcl-2 signal axis. Subsequently, the decrease of MMP induced mitochondria-mediated intrinsic apoptotic pathway and the overproduction of intracellular ROS in HepG2 cells, which contributed to cell apoptosis. Meantime, JPBP suppressed cell proliferation through promoting HepG2 cell cycle arrest in S phase. Collectively, this study sheds light on the potential application of JPBP on the prevention and therapy of hepatocellular carcinoma.